Two-component two-in-one adhesive mortar
Patent Information
- Application Number
- CN202611166972.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-10-27
AI Technical Summary
[0002]目前,建筑装饰及保温施工中通常需要分别使用界面处理剂、粘接砂浆和防水材料,施工过程中存在材料种类多、施工工序复杂、施工周期长以及不同材料之间相容性不足等问题,传统单组分水泥基粘接砂浆主要依靠水泥水化硬化形成粘结强度,其柔韧性和抗基层变形能力有限,在温度变化、干湿循环或基层轻微位移的条件下,容易出现空鼓、开裂和脱落现象
[0045]本发明采用粉料组分A与液料组分B分开包装,施工时按比例混合,能够减少现场加水造成的配比误差;普通硅酸盐水泥和白水泥提供主要胶凝强度,级配石英砂和重质碳酸钙形成稳定骨架并填充孔隙,粉煤灰和硅灰通过微集料填充及二次反应提高砂浆的密实性和抗渗性,可再分散乳胶粉、纯丙烯酸乳液和苯丙乳液共同形成聚合物改性结构,提高砂浆与混凝土、砌体、瓷砖、石材及保温板之间的粘结强度、柔韧性和耐水性,羟丙基甲基纤维素醚和淀粉醚改善保水性、施工性及抗流挂性能,聚丙烯纤维和木质素纤维分散并阻滞塑性收缩裂缝和干燥收缩裂缝,憎水剂降低材料吸水率,聚羧酸减水剂在保持施工和易性的同时降低拌合用水量,消泡剂减少有害气泡并提高硬化体密实度,缓凝剂延长可操作时间,防腐剂和冻融稳定剂提高液料组分的储存稳定性;各组分协同作用,使所得砂浆具有粘接、防潮和一定抗渗功能,能够减少空鼓、开裂、渗水及脱落现象,并具有施工工序少、适用基层范围广、施工配比稳定和耐久性较好的优点。
Abstract
Description
Technical Field
[0001] This invention relates to the field of mortar technology, and more specifically, to a two-component, two-in-one adhesive mortar. Background Technology
[0002] Currently, in building decoration and insulation construction, interface treatment agents, adhesive mortars and waterproof materials are usually required to be used separately. The construction process has problems such as many types of materials, complex construction procedures, long construction period and insufficient compatibility between different materials. Traditional single-component cement-based adhesive mortar mainly relies on cement hydration and hardening to form bonding strength. Its flexibility and resistance to substrate deformation are limited. Under conditions of temperature change, wet-dry cycle or slight displacement of the substrate, hollowing, cracking and falling off are easy to occur.
[0003] On the other hand, although some polymer-modified adhesive materials have good bonding performance and flexibility, they have problems such as insufficient open time, unstable water resistance, difficulty in controlling the construction ratio or high cost. Existing two-component materials may also have defects such as easy sedimentation after mixing powder and liquid components, insufficient workability, short construction time, slow bond strength development, and decreased bonding performance after long-term immersion in water.
[0004] Therefore, there is an urgent need for a two-component, two-in-one adhesive mortar to solve the above problems. Summary of the Invention
[0005] To overcome the aforementioned deficiencies of the prior art, embodiments of the present invention provide a two-component, two-in-one adhesive mortar. This invention uses separate packaging for powder component A and liquid component B, which are mixed proportionally during construction, reducing mixing errors caused by on-site water addition. Ordinary silicate cement and white cement provide the main cementitious strength; graded quartz sand and heavy calcium carbonate form a stable skeleton and fill pores; fly ash and silica fume improve the mortar's density and impermeability through micro-aggregate filling and secondary reaction; redispersible latex powder, pure acrylic emulsion, and styrene-acrylic emulsion together form a polymer-modified structure, improving the bonding strength, flexibility, and water resistance between the mortar and concrete, masonry, tiles, stone, and insulation boards. Hydroxypropyl methylcellulose ether... The mortar incorporates starch ether to improve water retention, workability, and anti-sagging properties; polypropylene fiber and lignin fiber to disperse and inhibit plastic shrinkage cracks and drying shrinkage cracks; a water-repellent agent to reduce the material's water absorption rate; a polycarboxylate superplasticizer to reduce mixing water consumption while maintaining workability; an antifoaming agent to reduce harmful bubbles and improve the density of the hardened body; a retarder to extend the workable time; and preservatives and freeze-thaw stabilizers to improve the storage stability of the liquid components. The synergistic effect of these components gives the resulting mortar adhesive, moisture-proof, and certain impermeability properties, reducing hollowing, cracking, water seepage, and detachment. It also offers advantages such as fewer construction steps, a wide range of applicable substrates, stable mix design, and good durability, thus addressing the problems mentioned in the background technology.
[0006] To achieve the above objectives, the present invention provides the following technical solution: a two-component two-in-one adhesive mortar, comprising powder component A and liquid component B, which are packaged independently;
[0007] The powder component A comprises the following components in parts by weight:
[0008] 30-50 parts of ordinary Portland cement;
[0009] 5-15 parts of white cement;
[0010] 25-45 parts graded quartz sand;
[0011] 5-15 parts of heavy calcium carbonate;
[0012] 2-8 parts fly ash;
[0013] 1-5 parts silica fume;
[0014] 2-8 parts of redispersible latex powder;
[0015] Hydroxypropyl methylcellulose ether, 0.1–0.5 parts;
[0016] 0.05–0.30 parts of polypropylene fiber;
[0017] 0.10–0.80 parts of lignin fiber;
[0018] Starch ether 0.02–0.20 parts;
[0019] Defoamer 0.05-0.30 parts;
[0020] 0.05–0.50 parts of polycarboxylate superplasticizer;
[0021] Water-repellent agent 0.10–1.00 parts;
[0022] 0.02–0.20 parts of retarder;
[0023] The liquid component B comprises the following components in parts by weight:
[0024] 25-50 parts of pure acrylic emulsion;
[0025] 5-20 parts of styrene-acrylic emulsion;
[0026] 25-55 parts water;
[0027] Film-forming aid 0.2–2.0 parts;
[0028] 0.1 to 1.0 parts of wetting and dispersing agent;
[0029] Defoamer 0.05-0.50 parts;
[0030] Preservative: 0.05–0.30 parts;
[0031] pH adjuster 0.05–0.50 parts;
[0032] Freeze-thaw stabilizer 0.2 to 2.0 parts.
[0033] In a preferred embodiment, the mass ratio of powder component A to liquid component B is 100:25 to 100:50, and the graded quartz sand includes quartz sand with particle sizes of 0.1-0.3 mm, 0.3-0.6 mm, and 0.6-1.2 mm.
[0034] In a preferred embodiment, the mass ratio of the quartz sand with particle sizes of 0.1–0.3 mm, 0.3–0.6 mm, and 0.6–1.2 mm is 25–45:35–55:10–30.
[0035] In a preferred embodiment, the redispersible latex powder is one or more of vinyl acetate-ethylene copolymer, vinyl acetate-vinyl acetate tert-carbonate copolymer, and acrylic acid copolymer.
[0036] In a preferred embodiment, the hydrophobic agent is one or more of calcium stearate, zinc stearate, sodium methylsilicate, and silane hydrophobic agents.
[0037] In a preferred embodiment, the pure acrylic emulsion has a solid content of 40% to 55% and a glass transition temperature of -20 to 20°C.
[0038] In a preferred embodiment, the ordinary silicate cement has a strength grade ≥42.5.
[0039] In a preferred embodiment, the pH adjuster is used to adjust the pH value of liquid component B to 7.5–9.0.
[0040] A method for preparing a two-component two-in-one adhesive mortar, characterized in that it includes any one of the above-mentioned two-component two-in-one adhesive mortars and the following steps:
[0041] Step 1: Premix the cement, graded quartz sand, heavy calcium carbonate, fly ash and silica fume in powder component A, then add redispersible latex powder, cellulose ether, fiber, starch ether, defoamer, polycarboxylate superplasticizer, water repellent and retarder, mix evenly to obtain powder component A;
[0042] Step 2: Mix water, wetting and dispersing agent, preservative, freeze-thaw stabilizer and film-forming aid, then add pure acrylic emulsion and styrene-acrylic emulsion, stir evenly, and after defoaming and pH adjustment, obtain liquid component B;
[0043] Step 3: Mix powder component A and liquid component B at a mass ratio of 100:25-50, stir evenly, and obtain the two-component two-in-one adhesive mortar.
[0044] The technical effects and advantages of this invention are as follows:
[0045] This invention uses separate packaging for powder component A and liquid component B, which are mixed in proportion during construction, reducing mixing errors caused by on-site water addition. Ordinary silicate cement and white cement provide the main cementitious strength, while graded quartz sand and heavy calcium carbonate form a stable skeleton and fill pores. Fly ash and silica fume improve the mortar's density and impermeability through micro-aggregate filling and secondary reaction. Redispersible latex powder, pure acrylic emulsion, and styrene-acrylic emulsion together form a polymer-modified structure, improving the bond strength, flexibility, and water resistance between the mortar and concrete, masonry, tiles, stone, and insulation boards. Hydroxypropyl methylcellulose ether and starch ether improve water retention. The mortar exhibits excellent workability and anti-sagging properties. Polypropylene and lignin fibers disperse and inhibit plastic shrinkage cracks and drying shrinkage cracks. Water-repellent agents reduce the material's water absorption rate. Polycarboxylate superplasticizers reduce the amount of mixing water while maintaining workability. Defoamers reduce harmful bubbles and improve the density of the hardened body. Retarder extends the workable time. Preservatives and freeze-thaw stabilizers improve the storage stability of liquid components. The synergistic effect of these components gives the resulting mortar adhesive, moisture-proof, and certain impermeability functions. It can reduce hollowing, cracking, water seepage, and detachment. It also has the advantages of fewer construction steps, a wide range of applicable substrates, stable construction mix ratios, and good durability. Detailed Implementation
[0046] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0047] This invention provides a two-component two-in-one adhesive mortar, comprising powder component A and liquid component B, which are packaged independently.
[0048] The powder component A comprises the following components in parts by weight:
[0049] 30-50 parts of ordinary Portland cement;
[0050] 5-15 parts of white cement;
[0051] 25-45 parts graded quartz sand;
[0052] 5-15 parts of heavy calcium carbonate;
[0053] 2-8 parts fly ash;
[0054] 1-5 parts silica fume;
[0055] 2-8 parts of redispersible latex powder;
[0056] Hydroxypropyl methylcellulose ether, 0.1–0.5 parts;
[0057] 0.05–0.30 parts of polypropylene fiber;
[0058] 0.10–0.80 parts of lignin fiber;
[0059] Starch ether 0.02–0.20 parts;
[0060] Defoamer 0.05-0.30 parts;
[0061] 0.05–0.50 parts of polycarboxylate superplasticizer;
[0062] Water-repellent agent 0.10–1.00 parts;
[0063] 0.02–0.20 parts of retarder;
[0064] The liquid component B comprises the following components in parts by weight:
[0065] 25-50 parts of pure acrylic emulsion;
[0066] 5-20 parts of styrene-acrylic emulsion;
[0067] 25-55 parts water;
[0068] Film-forming aid 0.2–2.0 parts;
[0069] 0.1 to 1.0 parts of wetting and dispersing agent;
[0070] Defoamer 0.05-0.50 parts;
[0071] Preservative: 0.05–0.30 parts;
[0072] pH adjuster 0.05–0.50 parts;
[0073] Freeze-thaw stabilizer 0.2 to 2.0 parts.
[0074] The mass ratio of powder component A to liquid component B is 100:25 to 100:50, and the graded quartz sand includes quartz sand with particle sizes of 0.1-0.3 mm, 0.3-0.6 mm, and 0.6-1.2 mm.
[0075] The mass ratio of the quartz sand with particle sizes of 0.1–0.3 mm, 0.3–0.6 mm, and 0.6–1.2 mm is 25–45:35–55:10–30.
[0076] The redispersible latex powder is one or more of vinyl acetate-ethylene copolymer, vinyl acetate-vinyl acetate tert-carbonate copolymer, and acrylic acid copolymer.
[0077] The hydrophobic agent is one or more of calcium stearate, zinc stearate, sodium methylsilicate, and silane hydrophobic agents.
[0078] The pure acrylic emulsion has a solid content of 40% to 55% and a glass transition temperature of -20 to 20°C.
[0079] The strength grade of the ordinary silicate cement is ≥42.5.
[0080] The pH adjuster is used to adjust the pH value of liquid component B to 7.5-9.0.
[0081] A method for preparing a two-component two-in-one adhesive mortar, characterized in that it includes any one of the above-mentioned two-component two-in-one adhesive mortars and the following steps:
[0082] Step 1: Premix the cement, graded quartz sand, heavy calcium carbonate, fly ash and silica fume in powder component A, then add redispersible latex powder, cellulose ether, fiber, starch ether, defoamer, polycarboxylate superplasticizer, water repellent and retarder, mix evenly to obtain powder component A;
[0083] Step 2: Mix water, wetting and dispersing agent, preservative, freeze-thaw stabilizer and film-forming aid, then add pure acrylic emulsion and styrene-acrylic emulsion, stir evenly, and after defoaming and pH adjustment, obtain liquid component B;
[0084] Step 3: Mix powder component A and liquid component B at a mass ratio of 100:25-50, stir evenly, and obtain the two-component two-in-one adhesive mortar.
[0085] Example 1
[0086] Powder component A includes:
[0087] 42 parts of ordinary Portland cement;
[0088] 8 parts white cement;
[0089] 30 parts graded quartz sand;
[0090] 8 parts of heavy calcium carbonate;
[0091] 4 parts fly ash;
[0092] Two parts silica fume;
[0093] 4 parts redispersible latex powder;
[0094] 0.25 parts of hydroxypropyl methylcellulose ether;
[0095] 0.15 parts of polypropylene fiber;
[0096] 0.30 parts of lignin fiber;
[0097] 0.08 parts of starch ether;
[0098] 0.12 parts of defoamer;
[0099] 0.20 parts of polycarboxylate superplasticizer;
[0100] 0.60 parts of water-repellent agent;
[0101] 0.10 parts of retarder.
[0102] Liquid component B includes:
[0103] 38 parts of pure acrylic emulsion;
[0104] 10 parts of styrene-acrylic emulsion;
[0105] 47 parts water;
[0106] 1.0 part of film-forming aid;
[0107] 0.5 parts wetting and dispersing agent;
[0108] 0.15 parts of defoamer;
[0109] 0.15 parts of preservative;
[0110] pH adjuster 0.20 parts;
[0111] 1.0 part of freeze-thaw stabilizer.
[0112] Powder component A and liquid component B are mixed at a mass ratio of 100:35.
[0113] This embodiment uses ordinary silicate cement, white cement, and graded quartz sand to form a cement-based skeleton. Fly ash, silica fume, and heavy calcium carbonate are added to improve particle size distribution and fill internal pores, thus enhancing the mortar's density and early strength. Redispersible latex powder synergistically forms a polymer-modified structure with the pure acrylic emulsion and styrene-acrylic emulsion in the liquid components, enhancing the adhesion and water resistance between the mortar and concrete, masonry, ceramic tiles, and stone substrates. Hydroxypropyl methylcellulose ether, starch ether, and fiber components improve water retention, workability, and crack resistance. A water-repellent agent reduces capillary water absorption, while polycarboxylate superplasticizer and defoamer improve the slurry's fluidity and the density of the hardened body. Therefore, this embodiment features a relatively balanced strength, adhesion, crack resistance, impermeability, and workability, making it suitable for bonding ceramic tiles, stone, and decorative panels to general indoor and outdoor walls, floors, concrete, and masonry substrates.
[0114] Example 2
[0115] Powder component A includes:
[0116] 38 parts of ordinary Portland cement;
[0117] 10 parts white cement;
[0118] 32 parts graded quartz sand;
[0119] 7 parts of heavy calcium carbonate;
[0120] 4 parts fly ash;
[0121] 3 parts silica fume;
[0122] 5.5 parts of redispersible latex powder;
[0123] 0.30 parts of hydroxypropyl methylcellulose ether;
[0124] 0.20 parts of polypropylene fiber;
[0125] 0.40 parts of lignin fiber;
[0126] 0.10 parts of starch ether;
[0127] 0.15 parts of defoamer;
[0128] 0.25 parts of polycarboxylate superplasticizer;
[0129] 0.70 parts of water-repellent agent;
[0130] 0.12 parts of retarder.
[0131] Liquid component B includes:
[0132] 42 parts of pure acrylic emulsion;
[0133] 8 parts of styrene-acrylic emulsion;
[0134] 45 parts water;
[0135] 1.2 parts of film-forming aid;
[0136] 0.6 parts of wetting and dispersing agent;
[0137] 0.20 parts of defoamer;
[0138] 0.15 parts of preservative;
[0139] pH adjuster 0.20 parts;
[0140] 1.2 parts freeze-thaw stabilizer.
[0141] Powder component A and liquid component B are mixed at a mass ratio of 100:40.
[0142] This embodiment increases the dosage of redispersible latex powder, pure acrylic emulsion, and fiber components, and appropriately increases the proportion of silica fume and liquid components, resulting in a more continuous polymer-modified and fiber-reinforced structure after the powder and liquid components are mixed. Specifically, the redispersible latex powder, pure acrylic emulsion, and styrene-acrylic emulsion improve the mortar's flexibility, interfacial wettability, bond strength, and water-resistant bonding performance. Polypropylene fibers and lignin fibers disperse internal stress and inhibit plastic shrinkage cracks and drying shrinkage cracks. Hydroxypropyl methylcellulose ether and starch ether improve water retention, anti-sagging, and construction performance. Therefore, this embodiment exhibits superior crack resistance, deformation adaptability, and substrate adhesion, reducing the risk of hollowing, cracking, and detachment caused by slight substrate deformation, temperature changes, or wet-dry cycles. It is suitable for exterior wall decoration, insulation board bonding, old wall renovation, and construction sites requiring high flexibility and crack resistance.
[0143] Example 3
[0144] Powder component A includes:
[0145] 46 parts of ordinary Portland cement;
[0146] 6 parts white cement;
[0147] 28 parts graded quartz sand;
[0148] 6 parts of heavy calcium carbonate;
[0149] 3 parts fly ash;
[0150] 3 parts silica fume;
[0151] 3 parts redispersible latex powder;
[0152] 0.20 parts of hydroxypropyl methylcellulose ether;
[0153] 0.10 parts of polypropylene fiber;
[0154] 0.20 parts of lignin fiber;
[0155] Starch ether 0.06 parts;
[0156] 0.10 parts of defoamer;
[0157] 0.15 parts of polycarboxylate superplasticizer;
[0158] 0.80 parts of water-repellent agent;
[0159] 0.08 parts of retarder.
[0160] Liquid component B includes:
[0161] 35 parts of pure acrylic emulsion;
[0162] 12 parts of styrene-acrylic emulsion;
[0163] 49 portions of water;
[0164] Film-forming aid 0.8 parts;
[0165] 0.4 parts wetting and dispersing agent;
[0166] 0.12 parts of defoamer;
[0167] 0.12 parts of preservative;
[0168] 0.15 parts pH adjuster;
[0169] 0.8 parts freeze-thaw stabilizer.
[0170] Powder component A and liquid component B are mixed at a mass ratio of 100:32.
[0171] This embodiment increases the relative amounts of ordinary silicate cement, silica fume, and water-repellent agent, and uses a lower proportion of polymer-modified components, resulting in a mortar with higher strength and a denser structure, forming a cement-based hardened body. Cement provides the main cementitious strength, silica fume and fly ash refine the pore structure through micro-aggregate filling and secondary reaction, graded quartz sand and heavy calcium carbonate improve the aggregate packing state, the water-repellent agent reduces capillary water absorption and water penetration, the defoamer reduces harmful internal pores, and the polycarboxylate superplasticizer reduces the amount of mixing water while ensuring construction fluidity. Therefore, this embodiment has better compressive strength, density, water resistance, and impermeability, and is suitable for underground engineering, equipment foundations, concrete structures, bathrooms, kitchens, balconies, and other areas with high requirements for moisture resistance, impermeability, and durability. Compared to Embodiment 2, its flexibility and crack resistance can be improved by controlling the construction thickness, base treatment, and curing conditions.
[0172] Table 1: Basic Construction Performance and Mechanical Properties of the Three Examples
[0173] Testing items Example 1 Example 2 Example 3 Workable time after mixing / h 1.50 1.67 1.33 Initial setting time / h 3.8 4.2 3.4 Final setting time / h 6.5 7.0 5.8 Tensile bond strength after 20 minutes of drying / MPa 1.18 1.30 1.20 Tensile bond strength after 30 minutes of drying / MPa 0.96 1.12 0.91 Initial tensile bond strength / MPa 1.36 1.53 1.45 Anti-slip / mm 0.35 0.25 0.40 28-day flexural strength / MPa 5.8 6.4 6.2 28-day compressive strength / MPa 32.5 30.8 36.7 28-line linear shrinkage rate / % 0.078 0.062 0.085
[0174] Table 2: Durability and Water Resistance of the Three Examples
[0175] Testing items Example 1 Example 2 Example 3 Tensile bond strength after immersion treatment / MPa 1.05 1.23 1.12 Tensile bond strength after heat aging treatment / MPa 1.10 1.28 1.17 Tensile bond strength after freeze-thaw cycles / MPa 1.02 1.20 1.10 Water immersion strength retention rate / % 77.2 80.4 77.2 Heat aging strength retention rate / % 80.9 83.7 80.7 Freeze-thaw strength retention rate / % 75.0 78.4 75.9 24h water absorption rate / % 7.8 6.5 5.6 Capillary water absorption rate / kg·m-2 0.42 0.34 0.28 Anti-seepage pressure / MPa 0.8 0.9 1.1 Surface crack condition No obvious cracks No obvious cracks No obvious cracks Maximum crack width / mm 0.08 0.05 0.10
[0176] This invention uses separate packaging for powder component A and liquid component B, which are mixed in proportion during construction, reducing mixing errors caused by on-site water addition. Ordinary silicate cement and white cement provide the main cementitious strength, while graded quartz sand and heavy calcium carbonate form a stable skeleton and fill pores. Fly ash and silica fume improve the mortar's density and impermeability through micro-aggregate filling and secondary reaction. Redispersible latex powder, pure acrylic emulsion, and styrene-acrylic emulsion together form a polymer-modified structure, improving the bond strength, flexibility, and water resistance between the mortar and concrete, masonry, tiles, stone, and insulation boards. Hydroxypropyl methylcellulose ether and starch ether improve water retention. The mortar exhibits excellent workability and anti-sagging properties. Polypropylene and lignin fibers disperse and inhibit plastic shrinkage cracks and drying shrinkage cracks. Water-repellent agents reduce the material's water absorption rate. Polycarboxylate superplasticizers reduce the amount of mixing water while maintaining workability. Defoamers reduce harmful bubbles and improve the density of the hardened body. Retarder extends the workable time. Preservatives and freeze-thaw stabilizers improve the storage stability of liquid components. The synergistic effect of these components gives the resulting mortar adhesive, moisture-proof, and certain impermeability functions. It can reduce hollowing, cracking, water seepage, and detachment. It also has the advantages of fewer construction steps, a wide range of applicable substrates, stable construction mix ratios, and good durability.
[0177] In conclusion, the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A two-component, two-in-one adhesive mortar, characterized in that, It includes powder component A and liquid component B, which are packaged separately from each other; The powder component A comprises the following components in parts by weight: 30-50 parts of ordinary Portland cement; 5-15 parts of white cement; 25-45 parts graded quartz sand; 5-15 parts of heavy calcium carbonate; 2-8 parts fly ash; 1-5 parts silica fume; 2-8 parts of redispersible latex powder; Hydroxypropyl methylcellulose ether, 0.1–0.5 parts; 0.05–0.30 parts of polypropylene fiber; 0.10–0.80 parts of lignin fiber; Starch ether 0.02–0.20 parts; Defoamer 0.05-0.30 parts; 0.05–0.50 parts of polycarboxylate superplasticizer; Water-repellent agent 0.10–1.00 parts; 0.02–0.20 parts of retarder; The liquid component B comprises the following components in parts by weight: 25-50 parts of pure acrylic emulsion; 5-20 parts of styrene-acrylic emulsion; 25-55 parts water; Film-forming aid 0.2–2.0 parts; 0.1 to 1.0 parts of wetting and dispersing agent; Defoamer 0.05-0.50 parts; Preservative: 0.05–0.30 parts; pH adjuster 0.05–0.50 parts; Freeze-thaw stabilizer 0.2 to 2.0 parts.
2. The two-component two-in-one adhesive mortar according to claim 1, characterized in that: The mass ratio of powder component A to liquid component B is 100:25 to 100:50, and the graded quartz sand includes quartz sand with particle sizes of 0.1-0.3 mm, 0.3-0.6 mm, and 0.6-1.2 mm.
3. The two-component two-in-one adhesive mortar according to claim 2, characterized in that: The mass ratio of the quartz sand with particle sizes of 0.1–0.3 mm, 0.3–0.6 mm, and 0.6–1.2 mm is 25–45:35–55:10–30.
4. The two-component two-in-one adhesive mortar according to claim 1, characterized in that: The redispersible latex powder is one or more of vinyl acetate-ethylene copolymer, vinyl acetate-vinyl acetate tert-carbonate copolymer, and acrylic acid copolymer.
5. The two-component two-in-one adhesive mortar according to claim 1, characterized in that: The hydrophobic agent is one or more of calcium stearate, zinc stearate, sodium methylsilicate, and silane hydrophobic agents.
6. The two-component two-in-one adhesive mortar according to claim 1, characterized in that: The pure acrylic emulsion has a solid content of 40% to 55% and a glass transition temperature of -20 to 20°C.
7. The two-component two-in-one adhesive mortar according to claim 1, characterized in that: The strength grade of the ordinary silicate cement is ≥42.
5.
8. The two-component two-in-one adhesive mortar according to claim 1, characterized in that: The pH adjuster is used to adjust the pH value of liquid component B to 7.5-9.
0.
9. A method for preparing a two-component, two-in-one adhesive mortar, characterized in that, Includes a two-component, two-in-one adhesive mortar as described in any one of claims 1-8, and the following steps: Step 1: Premix the cement, graded quartz sand, heavy calcium carbonate, fly ash and silica fume in powder component A, then add redispersible latex powder, cellulose ether, fiber, starch ether, defoamer, polycarboxylate superplasticizer, water repellent and retarder, mix evenly to obtain powder component A; Step 2: Mix water, wetting and dispersing agent, preservative, freeze-thaw stabilizer and film-forming aid, then add pure acrylic emulsion and styrene-acrylic emulsion, stir evenly, and after defoaming and pH adjustment, obtain liquid component B; Step 3: Mix powder component A and liquid component B at a mass ratio of 100:25-50, stir evenly, and obtain the two-component two-in-one adhesive mortar.